Predictive ability of the total score of the Kihon checklist for the incidence of functional disability in older Japanese adults: An 8‐year prospective study. Issue 9 (2nd August 2022) - Matsuzaki, Hideaki; Kishimoto, Hiro; Nofuji, Yu; Chen, Tao; Narazaki, Kenji
Abstract : Aim: To investigate the association between the total score of the Kihon checklist (t‐KCL score) and functional disability over an 8‐year follow‐up period, and to examine whether the t‐KCL score in the basic model with risk factors contributes to the incremental predictive ability for functional disability among older adults. Methods: We followed 2209 older adults aged ≥65 years without functional disability at baseline. The t‐KCL score was determined using a baseline survey questionnaire. Functional disability was defined based on information from long‐term care certifications. The association between the t‐KCL score and functional disability was examined using the Cox proportional hazards model. The incremental predictive ability of the t‐KCL score for functional disability was evaluated by the difference of the C‐statistic, category‐free net reclassification improvement (NRI), and integrated discrimination improvement (IDI). Results: The median follow‐up period was 7.8 years, and 557 participants developed functional disability. The adjusted hazard ratio (95% confidence interval [CI]) of functional disability for a 1‐point increase of the t‐KCL score was 1.08 (1.06–1.10). Adding the t‐KCL score to the basic model significantly improved the C‐statistic (95% CI) from 0.747 (0.728–0.768) to 0.760 (0.741–0.781). When the t‐KCL score was added to the basic model, the NRI and IDI were 0.187 (95% CI: 0.095–0.287) and 0.020 (95% CI: 0.012–0.027), respectively. Conclusions: The t‐KCL score had an independent positive association with functional disability over an 8‐year follow‐up. Furthermore, adding the t‐KCL score to the basic model improved the predictive ability for functional disability. Geriatr Gerontol Int 2022; 22: 723–729 . Abstract : An 8‐year prospective study on community‐dwelling older Japanese adults. A higher total score of the Kihon checklist (t‐KCL score) was associated with a higher risk of functional disability. The t‐KCL score improved the model's predictive ability for functional disability.